Predictors and Motivation for Seat Belt Use – A Case Study in Bosnia and Herzegovina - Zoran Injac; Milan Vujanić; Dalibor Pešić; Boris Antić (Promet - Traffic&Transportation, 2019)
The use of seat belts, for drivers and car occupants, results in reducing the rate of fatalities and severe road injuries. In this research, the methodology of the survey was applied through the self-reporting behaviour of the respondents who determined the subjective risk based on the attitudes of the traffic participants. To evaluate the statistical significance of the categorical variables, Pearson's chi-square test was used. For certain groups of examinees, the results of the relationship (association) between socio demographic characteristics were analysed as predictors of behaviour with the degree of seat belt use. Some other predictors of behaviour, such as the road and mood predictors were analysed as well. Interest was also focused on finding out what motivated certain groups of examinees to use the seat belt. Based on the results of this research, it is possible to classify the drivers and car occupants into certain groups with respect to the seat belt use while driving. This can help in determining the ways of eliminating problems related to the low degree of seat belt use.